Effect of Perceived Negative Workplace Gossip on Employees’ Behaviors - Kong, Ming (Frontiers in Psychology, 2018)
Negative workplace gossip generates social undermining and great side effects to employees. But, the damage of negative gossip is mainly aimed at the employee who perceived being targeted. The purpose of this study is to develop a conceptual model in which perceived negative workplace gossip influences employees’ in-role behavior and organizational citizenship behavior differentially by changing employees’ self-concept (organizational based self-esteem and perceived insider status). 336 employees from 7 Chinese companies were investigated for empirical analysis on proposed hypotheses, and results show that: (1) Perceived negative workplace gossip adversely influences employees’ IRB and OCB. (2) Self-concept (OBSE and PIS) plays a mediating role in the relationship between perceived negative workplace gossip and employees’ behaviors (IRB and OCB); (3) Employees’ hostile attribution bias moderates the relationship between perceived negative workplace gossip and self-concept (OBSE and PIS); and also moderates the mediating effect of self-concept (OBSE and PIS) on the relationship between perceived negative workplace gossip and employees’ behaviors (IRB and OCB). Thus, our findings provide deeper insights into the potential harmful effects of gossip. In addition, we help to explain the underlying mechanism and boundary condition of these effects.